Extension of Parent Company’s Liability against Third Parties of Subsidiary Company - Ms. Sulistiowati (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2011)
A parent company’s liability for their subsidiary’s third-party injury, which arises from its own instruction, is a major issue in the law on corporate groups. The ‘separate legal entity’, ‘limited liability’, and ‘limited liability within limited liability’ principles in a pyramidal corporate group construction are the causal factors of this legal complication.  Tanggung jawab induk perusahaan terhadap kerugian pihak ketiga dari anak perusahaan yang menjalankan instruksi induk perusahaan menjadi permasalahan hukum utama pada perusahaan kelompok. Tiga penyebab permasalahan tanggung jawab hukum dalam perusahan kelompok disebabkan oleh berlakunya prinsip separate legal entity, limited liability, maupun limited liability dalam limited liability pada konstruksi kelompok piramida.